2011
DOI: 10.1097/pgp.0b013e31821713b6
|View full text |Cite
|
Sign up to set email alerts
|

Misplaced Skeneʼs Glands

Abstract: So-called ectopic prostatic tissue in the cervix and vaginal tubulosquamous polyps are rare morphologically similar lesions that may show positive immunohistochemical staining with prostatic markers. It has been suggested that they are related to paraurethral Skene's glands that are the female equivalent of prostatic glands in the male. We report a large series of lesions in women aged 23 to 81 years, found within the cervix (n=24), vagina (n=10), and vulva (n=2), which we believe to be a part of a spectrum of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Prostatic-type tissue in the female genital tract is a phenomenon first described in the uterine cervix in 1997, 90 with subsequent literature expanding the clinicopathologic picture of the lesions. [91][92][93][94][95][96][97][98][99][100] The prostatic-type tissue is composed of glands identical in morphology and immunohistochemical staining to male prostatic glands, and frequently lined by basal cells (Figure 7, A). Early studies reported the presence of prostatic glands within the lamina propria of the uterine cervix, sparing the squamous epithelium, but with frequent and often extensive squamous metaplasia in the prostatic-type glands, with the potential for misdiagnosis as squamous cell carcinoma when identified deep within the stroma (Figure 7, B through D).…”
Section: Ectopic Prostate Tissue (Prostatic Metaplasia)mentioning
confidence: 99%
See 3 more Smart Citations
“…Prostatic-type tissue in the female genital tract is a phenomenon first described in the uterine cervix in 1997, 90 with subsequent literature expanding the clinicopathologic picture of the lesions. [91][92][93][94][95][96][97][98][99][100] The prostatic-type tissue is composed of glands identical in morphology and immunohistochemical staining to male prostatic glands, and frequently lined by basal cells (Figure 7, A). Early studies reported the presence of prostatic glands within the lamina propria of the uterine cervix, sparing the squamous epithelium, but with frequent and often extensive squamous metaplasia in the prostatic-type glands, with the potential for misdiagnosis as squamous cell carcinoma when identified deep within the stroma (Figure 7, B through D).…”
Section: Ectopic Prostate Tissue (Prostatic Metaplasia)mentioning
confidence: 99%
“…Most cases in these early studies were identified incidentally during evaluation of squamous intraepithelial lesions, with rare presentation as a clinically identified mass. 91 Immunohistochemically, the lesions have been reported to be reactive with prostate- specific antigen, [90][91][92][93][94][95]97,99,100 prostate-specific acid phosphatase, [90][91][92][93][94][95]97,100 androgen receptor, 99,100 NKX3.1, 98,99 and CK7. 99 High-molecular-weight CK shows positivity in the basal cell layer if present.…”
Section: Ectopic Prostate Tissue (Prostatic Metaplasia)mentioning
confidence: 99%
See 2 more Smart Citations